The efficiency of the agricultural economy digitalization - Kaldybayeva, D.O.; Bayadilova, D.M.; Koichubayev, A.S. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Object: Based on the analysis of the current economic state of agricultural development in the country and the level of use of digital factors, the degree of influence of the processes of agriculture digitalization on its efficiency was determined, the main problems of their implementation and development were assessed. Methods: Economic and statistical methods: comparison and correlation methods, logical and analytical methods. Results: An assessment of the main indicators development level of the country’s agricultural activity, as well as the digital factors use level were given. Using correlation analysis methods, the degree of connection between the pa-rameters of agriculture and the industry digitalization level was determined, a regression model was compiled with a predictive estimate of the next year parameters. Specific examples of the digital technologies use and the main problems in this area were considered. Conclusions: The study showed that the digital factors used in the country have a positive effect on agricultural performance indicators and have a high impact potential. However, currently in our country, it is insignificant, hardly noticeable and this process is not systematic, fragmented in terms of geography of application.
Ауыл шаруашылығы экономикасын цифрландыру тиімділігі
Эффективность цифровизации экономики сельского хозяйства
Keywords: digitalization; agriculture; efficiency; digital technologies; correlation; precision farming; digital fac-tors